Restraining the Demand Side Power Fluctuation of Active Distribution Network Using 0°/180° Phase Controlled Electric Spring. (2nd July 2018) - Chen, Yixi; Ma, Gang; Xu, Guchao; Chen, Huaiyi; Zhang, Hang
Abstract : In active distribution network, the random power output by wind/solar distributed generation may cause the stochastic fluctuation of demand side power, which will bring difficulties to power dispatching. In this paper, a method of restraining the demand side power fluctuation of active distribution network is proposed, in which a new power electronic device—electric spring—is applied by 0°/180° phase control strategy. Firstly, the basic principles of electric spring are introduced. Secondly, the reason for demand side power fluctuation of active distribution network is analyzed. After that, the 0°/180° phase control strategy of electric spring is proposed to restrain the demand side power fluctuation of active distribution network and the selection basis of noncritical loads is also obtained. The simulation results show that the method proposed in this paper is effective and the obtained selection basis of noncritical loads is reasonable.